Cachexia incidence, anemia and nutritional impact symptoms in cancer patients - da Rocha, Leoni Aparecida; Abe Vicente Cavagnari, Mariana; Rocha de Freitas Melhem, Angélica; Datsch Bennemann, Gabriela; Buzato Antunes, Lindsay Bianca; Gavarrete, Diogo; Schiessel, Dalton Luiz (O Mundo da Saúde, 2016)
Nutritional Impact Symptoms (NIS) and anemia are physiological changes commonly observed in cancer patients at earlier the diagnosis and during the radiotherapy and chemotherapy therapy that may interfere in general condition and cancer cachexia incidence. The goal of this study was evaluate cachexia, NIS and anemia incidence in cancer patients. It was evaluated, weight symptoms that interfere in food consumption and hemoglobin (usual/initial/ending period) in cancer patients attended in oncology clinic at Guarapuava-PR, linked to Brazil’s publicly funded health care system (SUS). It was enrolled 147 patients, and breast cancer was more prevalent (45.6%). Cachexia has been present in varying degrees at the diagnosis to treatment ending. Grouping by cancer type in treatment initial period, stomach cancer has shown the highest terminal cachexia percentage (n= 5, 31.3%) and breast cancer presented highest weight gain percentage (n = 25; 37.3%) with consequent reduction in cachexia subjects. At the treatment ending, stomach cancer patients remained highest terminal cachexia prevalence (n = 7; 43.8%) and breast cancer presented highest weight gain (n = 39; 58.2%). The most frequent NIS were xerostomia (n=84, 57.1%) and constipation (n=33, 22.4%). Between periods, stomach cancer patients have had higher of anemia percentage, respectively (n = 10, 62.5%; n = 11; 68.8%), and only breast cancer patients have had significant difference (p = 0.01). It was demonstrated in this study that greater cachexia degree is the most common incidence of anemia and symptoms of nutritional impact. It was evident in this study, high cachexia prevalence, frequent anemia and nutritional impact symptoms incidence.